28 Functional neurological disorder in the chronic pain clinic; a retrospective study of comorbidity. Issue 12 (14th November 2022) - Mason, Isabel; McWhirter, Laura; Carson, Alan; Stone, Jon; Hoeritzauer, Ingrid
Abstract : Objectives/Aims: Chronic pain is commonly reported as a comorbidity in patients with functional neurological disorder (FND) however the prevalence of FND in those presenting with chronic pain is unknown. We aimed to estimate 1) the prevalence of FND in patients seen at a chronic pain clinic and 2) how patients with chronic pain and comorbid FND differ from those without FND in terms of pain characteristics, psychiatric comorbidity, pain management and pain outcome. Methods: Retrospective electronic records review of consecutive new patients attending chronic pain clinics of 8 pain specialists in Lothian from the 1st of August 2019 to the 19thSeptember of 2019. Mean duration of follow up was 25 months. We recorded the clinical features, medication, management and outcome of chronic pain, any lifetime (up to November 2021) diagnoses of functional, FND and psychiatric disorders and undiagnosed neurological symptoms (where it was unclear if symptoms related to FND or another condition). Results: Of 190 patients attending a chronic pain clinic, 32 (17%) had at least one lifetime diagnosis of FND and an additional 8 (4%) had undiagnosed neurological symptoms. FND diagnoses were functional limb weakness (8%), functional sensory disorder (8%), dissociative seizures (6%), functional cognitive disorder (5%), functional movement disorder (4%) and others (2%). Chronic primary pain (p<0.001), widespread chronic primary pain (p<0.00001) and pain with no precipitating trigger (p<0.01) were more common in pain patients with comorbid FND. A history of depression (p<0.001), anxiety (p<0.05) and suicide attempt (p<0.05) were also more common in these patients. However, patients with chronic pain and comorbid FND did not differ significantly from patients without FND in age, gender, prescribed analgesia (opiates and benzodiazepines) or pain outcome (25% vs 34% pain improved). Conclusions: FND was found in a surprisingly high 17% of new patients at a chronic pain clinic. This may be an underestimate based on an additional 4% of patients with undiagnosed neurological symptoms. Patients with chronic pain and FND are significantly more likely to have chronic primary pain compared to other pain patients but do not experience different pain management or outcome. These results provide further evidence of the important overlap between FND and chronic pain conditions.